2016
DOI: 10.1016/j.heares.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Immune defense is the primary function associated with the differentially expressed genes in the cochlea following acoustic trauma

Abstract: Our previous RNA-sequencing analysis of the rat cochlear genes identified multiple biological processes and molecular pathways in the cochlear response to acoustic overstimulation. However, the biological processes and molecular pathways that are common to other species have not been documented. The identification of these common stress processes is pivotal for a better understanding of the essential response of the cochlea to acoustic injury. Here, we compared the RNA-sequencing data collected from mice and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 43 publications
(48 reference statements)
6
49
0
2
Order By: Relevance
“…The toxic cellular components released by dying sensory cells could cause an increased inflammatory response. This view is supported by a previous finding that SESN2 expression prevents inflammatory responses initiated by the activation of Toll-like receptors (Tlr) in macrophages (Yang et al, 2016). Tlr are a group of membrane sensor molecules that can detect both extrinsic molecules from bacteria and intrinsic molecules from damaged cells.…”
Section: Discussionsupporting
confidence: 61%
“…The toxic cellular components released by dying sensory cells could cause an increased inflammatory response. This view is supported by a previous finding that SESN2 expression prevents inflammatory responses initiated by the activation of Toll-like receptors (Tlr) in macrophages (Yang et al, 2016). Tlr are a group of membrane sensor molecules that can detect both extrinsic molecules from bacteria and intrinsic molecules from damaged cells.…”
Section: Discussionsupporting
confidence: 61%
“…While the magnitude of protection likely depends on the precise acoustic stimulus employed and the method of Z-VAD delivery, the collective data suggest that reliance on caspase cleavage is conserved between rodent and zebrafish models of acoustic trauma. Differential gene expression patterns have also been identified in noise-exposed cochlea ( Cho et al, 2004 ; Kirkegaard et al, 2006 ; Yang et al, 2016 ). The importance of protein synthesis in acoustic trauma is difficult to test in rodents due to the high systemic toxicity of protein synthesis inhibitors ( Hoffmann et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have found that noise induces mechanical trauma to the eighth cranial nerve, and surrounding structures, including the cochlea [10,11], and it has been proposed that during repair of these damages, DNA errors could be replicated during cell division, resulting in pathological proliferation [3]. The mechanical stress has also been proposed to entail subsequent biological and molecular stress, including oxidative stress, excitotoxity, and inflammation [11]. Rodent studies examining gene expression following acoustic overstimulation suggested that the primary pathways affected were immune and inflammatory pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical stress has also been proposed to entail subsequent biological and molecular stress, including oxidative stress, excitotoxity, and inflammation [11]. Rodent studies examining gene expression following acoustic overstimulation suggested that the primary pathways affected were immune and inflammatory pathways [11]. A study of noise exposure in zebrafish found genes involved in cell proliferation, apoptosis and immune functions to be significantly regulated in the inner ear after exposure [12].…”
Section: Introductionmentioning
confidence: 99%